(untitled) (CAHIERS MAGELLANES-NS, 2024)
Purpose – The purpose of this paper is evaluate the factors affecting the intention to use digital banking in Assam, India. Design/methodology/approach – Multivariate data analysis techniques (Structure equation model, Cronbach‟sAlpha test, Confirmatory Factor Analysis) were employed for the survey data collected from 201 customers who are well versed to digital banking. Findings – From the results of this study, it was found that perceived usefulness has a positive effect on attitude and intention to use the service. Therefore, it is necessary to enhance the sense of the usefulness of customers through media advertising and consulting so that customers fully understand the benefits brought about by using digital banking services Practical implications – Practical guidelines are provided to bank management on how to impact positively on consumer attitude to leverage migration to digital banking among actual customers who are nonusers or very rare users. Originality/value – There is a lack of studies evaluating factors affecting the intention of customer to use digital banking channels in rural region of Assam.